Development And Texture of Pulmonary Trunk in Children - Sadikova Z. Sh. (Scholars Digest Publishing, 2023)
We have studied texture and sites of pulmonary trunk in children (from the birth to 12 years of life). Experiments were carried out on 55 children's corpses. The following results were obtained: pulmonary trunk develops continuously and asynchronously: rapid growth process develops in children of an early age, diameter of pulmonary trunk increases from the first days of its existence and subsequently develops in its length. The wall of pulmonary trunk became thicker 2,1 times on the average but this growth does not depend on increase in its size. Pillow-shaped formation and protrusion into a wall of pulmonary trunk is contributing to more rapid blood flow into the lungs.